Antecipação da colheita de trigo pela dessecação química e a influência na qualidade de sementes - Fipke, Glauber Monçon (2018)
In order to reduce the time of exposure to abiotic factors after the physiological maturity of the wheat, pre-harvest desiccation may be a practice for obtaining quality seeds. The aim of this work was evaluated as a possibility to anticipate a wheat harvest for the application of non-selective herbicides in the pre-harvest and its effects on seed production. For this, three experiments were carried out in the Departamento de Fitotecnia (UFSM) using BRS Parrudo and TBIO Sinuelo cultivars. The first experiment consisted of a field research evaluating the agronomic characters and the economic viability. With the seeds obtained in the first experiment, the second and third experiments were carried out under controlled conditions on seed laboratory (physical, physiological and sanitary quality) and plant physiology (seedling morphology and enzymatic activity), respectively. The treatments were distributed in a factorial experiment plus additional treatment (3x4+1). In the first factor, the herbicides (glufosinate-ammonium, glyphosate and paraquat) were allocated, at second factor were allocated the phenologicals stages for herbicide applications (83, 85, 87, 92) and control (without application). In experiment 1, the pre-harvest desiccation with non-selective herbicides in the cultivar TBIO Sinuelo provided a mean yield reduction of 413 kg ha-1 in relation to the control; the mass of the hectoliter was not influenced; there was an average reduction of 11% in the seed mass. In experiment 2, there was an 8% and 26% reduction in germination under controled conditions for BRS Parrudo and TBIO Sinuelo, respectively, by the use of herbicides. Soil germination was 14% higher for the control treatment. In the experiment 3, the application of herbicides at the phenological stage 83 reduced the length (8.4 mm) and the projected area (1.3 mm2) in relation to the other phenological stages. The activity of the enzyme superoxide dismutase was not influenced by herbicide treatments. The herbicide glyphosate increases the activity of the guaiacol peroxidase enzyme in 45 and 43% for both cultivars. The main conclusions are: the application of the non-selective herbicides glufosinate-ammonium (350 g a.i. ha-1) and paraquat (400 g a.i. ha-1) in the pre-harvest promoted greater phytointoxication of the wheat, anticipating the harvest in 4.8 and 5.3 days, respectively. There is a reduction in seed yield and seed mass, with no economic feasibility for both cultivars evaluated (Experiment 1); the seeds seeds from plants that have been desiccated in the pre-harvest have deterioration more pronounced and the physiological quality expressed by the germination is impaired, negatively affecting the vigor in optimal conditions and also of stress. There is no interference in seed sanitary conditions (Experiment 2); the morphology of the shoot and the root are negatively affected by increased enzymatic activity and hydrogen peroxide content in seedlings coming from the plants seeds desiccateds in the preharvest (Experiment 3). Therefore, the pre-harvest desiccation of wheat with the benefit of anticipating the harvest in a few days is not justified.